THE INSTITUTIONAL DEFICIT IN WATER GOVERNANCE OF THE MEKONG RIVER AND ITS IMPLICATIONS FOR VIETNAM - Thi Quynh Huong, Tong; Khanh Thai An, Nguyen (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
This paper examines the institutional deficiencies in water governance across the Mekong River Basin and their profound impacts on Vietnam, the lowest downstream country and one of the most vulnerable to hydrological changes. By synthesizing secondary sources and comparing four key regional cooperation mechanisms (MRC, GMS, LMC, and LMI), the study reveals that the existing institutional network in the Mekong Basin remains fragmented, legally non-binding, and lacks effective coordination. These weaknesses have resulted in asymmetrical power relations, uneven benefit-sharing, and increased ecological and social vulnerability in downstream areas, particularly the Mekong Delta in Vietnam. By interdisciplinary research methods, historical methods, policy analysis methods, etc, the paper explores Vietnam’s multi-level responses, including regional water diplomacy, bilateral and multilateral cooperation, and domestic adaptation policies. It argues that the root cause of the current crisis lies not only in the upstream states’ exploitation but also in the structural insufficiency of basin-wide governance mechanisms. Strengthening institutional capacity and establishing a transparent, equitable, and sustainable framework for transboundary water management are therefore essential to ensure the long-term resilience of the Mekong Basin.